The Effect of Perception of Security, Easy of Transaction, and Shopping Experience on Purchase Decision and its Implications on Customers Satisfaction (Case Study of Geraipedia Jabodetabek Customers) - Melitina Tecoalu; Soegeng Wahyoedi; Edwind Kustiawan (Primanomics : Jurnal Ekonomi & Bisnis, 2021)
This study discusses the perception of security, ease of transaction, and ease of shopping for purchasing decisions, as well as the implications of purchasing decisions on Geraipedia customer satisfaction. This research discusses some of the problems that Geraipedia has experienced. The first problem is related to security, namely the leakage of Geraipedia user data circulating in the media. This has been acknowledged by Geraipedia, that it was true that 91 million customer data has been leaked. The data includes encrypted customer passwords, customer names, e-mail addresses, date of birth, and telephone numbers. Second, Geraipedia itself had a problem with an error payment system. Transactions made by customers are considered unsuccessful. However, the solutions provided by Geraipedia are unclear, not detailed, and unresponsive so that the customer shopping experience is not good. If the above problems are not resolved, then other problems arise related to transaction security, ease of transactions, and customer shopping experience. These problems will affect customer purchasing decisions on Geraipedia, so this customer purchase decision will affect Geraipedia customer satisfaction.The first hypothesis in this study is the influence of security perceptions on purchasing decisions on Geraipedia. The results showed that the security perception variable had no effect on the purchasing decision variable with a t-statistic of 0.318 <1.96 and a significance value of 0.750> 0.05. The second hypothesis in this study is the effect of ease of transaction on purchasing decisions on Geraipedia. The results showed that the variable transaction ease had an effect on the purchasing decision variable with a t-statistic of 5.843> 1.96 and a significance value of 0.00 <0.05. The third hypothesis in this study is the influence of shopping experience on purchasing decisions on Geraipedia. The results showed that the shopping experience variable had a positive effect on the purchasing decision variable with a t-statistic of 7.898> 1.96 and a significance value of 0.00 <0.05. The fourth hypothesis in this study is the influence of purchasing decisions on customer satisfaction in Geraipedia. The results showed that the purchasing decision variable had an influence on the customer satisfaction variable with a t-statistic of 12.197> 1.96, with a significance value of 0.00 <0.05.